Perbedaan Kemampuan Penalaran Matematis dan Kemandirian Belajar Siswa Melalui Pembelajaran TPS Berbantu Autograph dan Media Gambar - Merna wati (Edumaspul: Jurnal Pendidikan, 2020)
This study aims to determine the differences in increasing mathematical reasoning abilities and self-regulated learning through Think Pair Share (TPS) learning using Autograph and drawing tools. This type of research is a quasi-experimental. The population in this study were all students of class XI of SMA Negari 1 Lawe Alas totaling 60 students. The selection of research samples is determined by randomly selecting two classes. The instrument used in data collection consisted of tests of mathematical reasoning abilities and students' regulated learning. The test of learning outcomes in the form of essays that have been tested for validity, reliability, power difference, and level of difficulty. Data analysis technique uses two-way ANOVA. The results showed that there were differences in increasing mathematical reasoning abilities and student regulated-learning through TPS learning using Autograph and drawing tools.In addition, there was an interaction between students' initial abilities with the TPS learning model using Autograph on students' mathematical reasoning abilities and students' reglated-learning.